The state of food and agriculture 2002 (FAO agriculture series, 2002)
Reports on current developments and issues in world agriculture. Monitors the global agricultural situation as well as the overall economic environment surrounding world agriculture. Presents and overview of the status of negotiations on agricultural trade following the launching of the World Trade Organization's new round of multilateral trade negotiations. Discusses how public goods such as agriculture, fisheries and forestry properly managed can provided benefits to large sections of people. Calls for increased international inflow of funds towards agriculture and rural areas, in order to promote globally the provision of these public goods